Dynamic expiratory airway collapse and evaluation of collateral ventilation with Chartis - Shah, Pallav; Herth, Felix (Thorax, 2014)
We thank Gesierich et al 1 for raising some important issues regarding the evaluation of collateral ventilation using the Chartis flow catheter. In our review, we only provided two classical examples of Chartis expiratory flow and inspiratory pressure results; one from a patient with no collateral ventilation and another from a patient with significant collateral ventilation.2 However, in clinical practice, a range of findings are observed that sit in the ‘grey zone’. - - In our practice and the results from an open-label multicentre study of valves where collateral ventilation was assessed with the Chartis system, it is evident that adequate assessment was not possible in about 15% of patients.3 A variety of factors may be responsible. Blockage of the catheter by secretions or apposition of the catheter against …